BASIC CONCEPT, MANAGEMENT, AND BUDGETING OF PUBLIC FINANCE IN ISLAMIC EDUCATION - Yahya, Yafi'u; Sarono, Agus (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This study provides conceptual, contextual, and correlational explanations of public finance in Islamic education. In order to investigate public finance in Islamic education from the perspectives of idea, background, and correlation, this study employed a qualitative methodology. Descriptive analysis was employed in the study data analysis. The procedure involved gathering data up until the point of fieldwork, at which point the researcher started the process of analysis and completed it. This study came to the conclusion that transparent and accountable management of public finances, or state finances, is necessary, particularly when it comes to execution, accountability, and conduct. Since public finance management is both religious and economic, it ought to be able to raise general welfare. Even though Indonesia's state budget management system has undergone reforms recently, including the adoption of a state finance constitution and a shift from a balanced and dynamic budget system to one based on performance, other changes point to the government's serious attempts to manage public finances. The changes in budget types - rom routine and development budgets to routine budgets alone—also reflect these reforms. By considering the public interest in providing facilities and supporting infrastructure, as well as by managing state revenues in accordance with applicable laws and without engaging in irregularities when obtaining income and spending for the public, budget management in public finance, or state finances, seeks to create public welfare. The state's responsibility in overseeing public finances is to uphold the law and give the populace social security. Public facilities are required to accomplish this purpose, as is close oversight by qualified and reputable state authorities to guarantee that public revenue is distributed in an appropriate and equitable manner.